A Challenging Case: Colorectal Cancer During Pregnancy - Caesar Ahmad Tidel; Syifa Mustika (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2023)
Introduction: Colorectal cancer (CRC) occurring in younger women can lead to an increased incidence of colorectal cancer during pregnancy. The estimated frequency of malignancy during pregnancy with colorectal cancer specifically estimated at 1 in 13,000 pregnancies. However, the exact causes of colorectal cancer during pregnancy are not yet fully understood. Diagnosing and managing colorectal cancer during pregnancy pose significant challenges because the symptoms can be masked by the normal signs and symptoms of pregnancy. Case Pesentation: A 42-year-old pregnant patient, Mrs. L, presented with abdominal pain, a history of dark-colored bowel movements, and a lump on the left side of her neck that had been present for a year. She had also experienced a weight loss of 5 kg both before and during pregnancy, and there was no previous history of malignancy. The patient underwent various diagnostic procedures, including pregnancy ultrasound, abdominal ultrasound, and colonoscopy biopsy. Based on the comprehensive evaluation of the patient's medical history, physical examination, and supporting tests, she was diagnosed with stage IV rectal adenocarcinoma with metastases to the liver, kidney, and lymph nodes. The patient was in her second pregnancy (G2P1Ab0) at 27-29 weeks of gestation. Conclusion: Colorectal cancer during pregnancy poses diagnostic and therapeutic challenges, as the signs and symptoms are often attributed to the normal progression of pregnancy, resulting in delayed diagnosis at an advanced stage. Early detection, evaluation, and monitoring of nonspecific symptoms are crucial, and a multidisciplinary approach is necessary for the management of colorectal cancer during pregnancy.